1997
DOI: 10.1128/jvi.71.11.8642-8656.1997
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the CCR5 genes of African green monkeys and mice implicate specific amino acids in infections by simian and human immunodeficiency viruses

Abstract: CCR5, a receptor for the CC chemokines RANTES, Mip1␣, and Mip1␤, has been identified as a coreceptor for infections by macrophage-tropic isolates of human immunodeficiency virus type 1 (HIV-1). To study its structure and function, we isolated cDNA clones of human, African green monkey (AGM), and NIH/Swiss mouse CCR5s, and we quantitatively analyzed infections by macrophage-tropic HIV-1 and SIV mac251 after transfecting human HeLa-CD4 cells with the CCR5 expression vectors. The AGM and NIH/Swiss mouse CCR5 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…It is interesting that the AGM population harbors a CCR5 allele which contains the D13N mutation, which plays an important role in CD4-independent SIV infection (39). Since SIV is thought to have existed in the AGM population for many generations, it has been hypothesized that mutations in CCR5 are likely to occur in regions of CCR5 which limit SIV pathogenicity (39). Interestingly, a separate study found that in four of four sooty mangabeys examined, CCR5 contained the S180P mutation, which we also found to limit CD4-independent virus infection (10).…”
Section: Discussionmentioning
confidence: 54%
“…It is interesting that the AGM population harbors a CCR5 allele which contains the D13N mutation, which plays an important role in CD4-independent SIV infection (39). Since SIV is thought to have existed in the AGM population for many generations, it has been hypothesized that mutations in CCR5 are likely to occur in regions of CCR5 which limit SIV pathogenicity (39). Interestingly, a separate study found that in four of four sooty mangabeys examined, CCR5 contained the S180P mutation, which we also found to limit CD4-independent virus infection (10).…”
Section: Discussionmentioning
confidence: 54%
“…Amino acid sequence alignments of CCR5 derived from people of diverse genetic backgrounds show that this chemokine receptor is highly conserved (2,50). Similarly, despite the high frequency of amino acid polymorphism for CCR5 alleles derived from nonhuman primates, including apes, Old World monkeys, New World monkeys, and selected prosimians, we observed amino acid conservation within specific regions, especially within the chemokine receptor ectodomain (4,9,34,43,50). All of these characterized nonhuman primate CCR5 alleles permit primate immunodeficiency virus fusion and entry (34, 35a, 43) and thus likely permit the cross-species transmission of primate immunodeficiency virus (8,47).…”
mentioning
confidence: 67%
“…The ability to replicate in primary human lymphocytes has been observed for other SIVs [11]. In addition, almost all other SIVs studied up to now, including SIVcpz-gabl, also use CCR5 and not CXCR4 [2,7,16]. The exceptions reported so far concern SIVrcm and SIVmind-GB1.…”
Section: Discussionmentioning
confidence: 90%